Two treatises of government - Locke, John, 1632-1704; Laslett, Peter (Cambridge : Cambridge University Press, 1988)
This is the revised version of Peter Laslett's acclaimed edition of Two Treatises of Government, which is widely recognised as one of the classic pieces of recent scholarship in the history of ideas, read and used by students of political theory throughout the world. This 1988 edition revises Dr Laslett's second edition (1970) and includes an updated bibliography, a guide to further reading and a fully reset and revised introduction which surveys advances in Locke scholarship since publication of the second edition. In the introduction, Dr Laslett shows that the Two Treatises were not a rationalisation of the events of 1688 but rather a call for a revolution yet to come.
Foreword -- Introduction -- 1: Book -- 2: Locke the man and Locke the writer -- 3: Two treatises of government and the revolution of 1688 -- 4: Locke and Hobbes -- 5: Social and political theory of two treatises of government -- Addendum: the dating of the composition of two treatises -- Editorial note -- Text -- Preface -- First treatise -- Second treatise -- Suggested reading -- Bibliography -- Index.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Political science -- Early works to 1800.; Liberty